Genre and Stylistic Features of Correspondence T. G. Shevchenko (Linguostylistic Studies, 2015)
The article discusses epistolyary Shevchenko as an artistic phenomenon. Attention is drawn to the genre and stylistic features of his correspondence, thematic palette. Analyzed a range of informative letters submitted their classification: a letter-request: a) about everyday things: about the shirt Plahtiy, ribbons; b) about the book; c) the work of the university; Letter-Apology; Letter-self-criticism; Letter-poludialog; letter-gratitude; letter-proposal. Investigated epistles, in which a request is combined with the promise of an apology, thanks. Special attention to the epistolary Bard deserve intimate letters, especially to the east Repnina. Intimate discourse gives the opportunity to know and feel the psychological depth, sensual dominant and exceptional tonal directness letters with their emotional and psychological tension. Key words: epistolary journalism, epistolyary, epistles, humanism, patriotism, genre specificity, thematic range, stylistic features. References